Cross-border lending and the international transmission of banking crises - Daniel Dieckelmann (Freie Universität Berlin, School of Business & Economics, 2020)
This paper introduces a new transmission channel of banking crises where sizable cross-border bank claims on foreign countries with high domestic crisis risk enable contagion to the home economy. This asset-side channel opposes traditional views that see banking crises originating from either domestic credit booms or from cross-border borrowing. I propose a combined model that predicts banking crises using both domestic and foreign factors. For developed economies, the channel is predictive of crises irrespective of other types of capital ows, while it is entirely inactive for emerging economies. I show that policy makers can significantly enhance current early warning models by incorporating exposure-based risk from cross-border lending.
urn:nbn:de:kobv:188-refubium-27771-8
Keywords: C53; E44; F34; G01; G21; 330; cross-border bank lending; banking crises; systemic risk; financial linkages